Navigating Talent Development in the Public Sector: Insights from a Literature Review - Martins, Rosena Fatima De Oliveira (JUSTBEST Journal of Sustainable Business and Management, 2025)
Talent management in the public sector is crucial for enhancing organizational effectiveness, improving service delivery, and ensuring that public institutions can meet the evolving needs of society. This literature review explores the challenges and strategies related to talent development in the public sector. It examines the barriers to recruitment and retention, the importance of leadership development, employee engagement, and the integration of technology into talent management practices. Public sector organizations often face difficulties in attracting top talent due to budget constraints, political influences, and competition from the private sector. Leadership development programs are essential to equip leaders with the skills needed to manage diverse teams and navigate political complexities. Furthermore, employee engagement and retention strategies, including fostering work-life balance and professional development opportunities, are crucial for ensuring a motivated and skilled workforce. The review also highlights the growing role of technology in streamlining talent management processes and improving efficiency. Despite progress, gaps remain in region-specific research, particularly in developing countries, and in addressing mid-career professionals and succession planning. This review provides valuable insights for policymakers, public sector leaders, and human resource professionals to optimize talent management strategies and ensure the success of public sector organizations.